2011
DOI: 10.3109/13880209.2011.611811
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic activity of the marine diatomCocconeis scutellumand eicosapentaenoic acid in BT20 cells

Abstract: (2012) Apoptotic activity of the marine diatom Cocconeisscutellum and eicosapentaenoic acid in BT20 cells, Pharmaceutical Biology, 50:4, 529-535,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Several studies have reported biological activities of fatty acids from various microalgal species, like anti-bacterial [105,106,107] andanti-cancer activities [108]. Further characterization of the lipid content in the total jellyfish extract (TE) and its fractions is in progress.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported biological activities of fatty acids from various microalgal species, like anti-bacterial [105,106,107] andanti-cancer activities [108]. Further characterization of the lipid content in the total jellyfish extract (TE) and its fractions is in progress.…”
Section: Resultsmentioning
confidence: 99%
“…Microalgae have a great potential for the production of bioactive molecules of pharmaceutical interest [1,2,3,4,5]. Particularly, microalgal pigments protect normal cells from genetic damages and exert antiproliferative, cytotoxic and pro-apoptotic activities in cancer cells, suggesting their possible use for cancer prevention or chemiotherapy [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In Table 2, we report the microalgae for which the most abundant PUFAs produced were studied. Several biological functions have been associated to DHA and EPA, such as a wide range of beneficial cardiovascular effects [82], antimicrobial activities [83], anti-inflammatory modulation [84], antioxidant properties [85], beneficial effects on respiratory diseases [86,87], antitumoral activity [88], and inflammation attenuation in adipose tissues [89]. Different authors highlighted the immune-stimulatory properties of PUFA [90,91], as well as their anti-inflammatory properties [92].…”
Section: Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 99%